Investigating the relationship between Pfkelch13 mutations and response to artemisinin-based treatment for uncomplicated falciparum malaria: a protocol for a systematic review and individual patient data meta-analysis - Prabin Dahal; Philippe Guerin; Farhad Shokraneh; James A Watson; Karen I Barnes; Aboubakar Soma; Stephanie van Wyk; Chistevy Vouvoungui; Dhol S Ayuen (BMJ Open)
Introduction Artemisinin-based combination therapies (ACTs) remain the WHO-recommended treatment for uncomplicated Plasmodium falciparum malaria. However, the emergence and spread of artemisinin resistance (ART-R) threatens ACT efficacy. ART-R is phenotypically expressed as delayed parasite clearance, which can facilitate ACT partner drug resistance. ART-R has been causally linked to specific mutations in the Pfkelch13 gene.Methods and analysis The systematic review and associated meta-analysis aim to determine the correlation between Pfkelch13 (alleles present in the Kelch13 gene region of the P. falciparum parasite) genotypes and clinical and parasitological response to ACTs from a globally representative data set pooling individual patient data (IPD) from eligible published and unpublished studies. The eligibility criteria include Pfkelch13 genotyping results at baseline complemented by individually linked parasitological and clinical assessments following artemisinin-based treatment. The data will be curated, standardised and analysed using this proposed statistical analysis plan (SAP), adhering to PRISMA-IPD (PRISMA, Preferred Reporting Items for Systematic reviews and Meta-Analyses) guidelines. Our SAP will apply hierarchical modelling to assess the effect of the P. falciparum parasite Pfkelch13 mutations on parasite clearance half-life and therapeutic efficacy across different regions. This will include study sites as random effects in the model and potential predictors such as age, sex, baseline parasite load and other potential effect modifiers as fixed effects. This analysis will enhance the understanding of the influence of Pfkelch13 mutations on malaria treatment outcomes.Ethics and dissemination Data were obtained with informed consent and ethical approvals from the relevant countries and were pseudonymised before curation in the Infectious Diseases Data Observatory (IDDO)/WorldWide Antimalarial Resistance Network (WWARN) repository. Data ownership remains with contributors. This IPD meta-analysis met the Oxford Tropical Research Ethics Committee criteria for waiving ethical review, as it is a secondary analysis of existing pseudonymised data. The resulting peer-reviewed publication and conference proceedings will help strengthen and enhance the efficiency of ART-R surveillance and response and support policy decisions.PROSPERO registration number CRD42019133366.